A Class of Nonlinear Degenerate Parabolic Equations Not in Divergence Form (Communications in Mathematical Research, 2021)
This paper is devoted to the study of a class of singular nonlinear diffusionproblem. The existence and uniqueness of solutions are obtained. Moreover, someproperties of solutions such as blow-up property etc. are also discussed.
Keywords: singularity; diffusion; existence; uniqueness.